Priority-based minimum interference channel assignment technique for multi-radio multi-channel wireless mesh networks - Raja Bongsu, Raja Hasyifah; Muhammed, Abdullah; Subramaniam, Shamala; Mohamed, Mohamad Afendee (Newswood, 2023)
Wireless mesh networks (WMN) have been attracting the interest of many researchers in these recent years. Several researchers worked on the optimisation of network performances for multi-radio multi-channel WMN with constrained channel resources. Others demonstrated that partially overlapping channels could expand these limited resources. Where there are insufficient resources, interfered links may significantly impact the capabilities of the channel. The problems of channel assignment have been considered NPhard problems. A PRIority-based Minimum Interference Channel Assignment (PRIMICA) algorithm has been developed to minimise the effect of interference on WMN efficiency by assigning the radio to the least-interfering available channel. Channels are assigned based on the priority weight of the interfering node with the lowest value. The proposed algorithm outperformed network throughput, packet loss ratio, and end-to-end delay, as demonstrated by performance simulation.